Clinical characteristics and outcomes of Korean patients with sarcoidosis - Ho Jeong Kim; Hyeong Min Kim; Jin Woo Song (Scientific Reports, 2021)
Abstract Sarcoidosis is a systemic granulomatous disorder of unknown cause involving multiple organs. Its clinical presentation and prognosis vary among races. We identified the clinical characteristics and outcomes of Korean patients with sarcoidosis. Clinical data of 367 Korean patients with biopsy-proven sarcoidosis diagnosed in 2001–2017 were retrospectively analyzed. Treatment responses included improvement, stability, or progression based on changes in pulmonary sarcoidosis on chest images. The mean age was 47.4 years, and 67.3% of patients were women. The median follow-up period was 80 months. The highest prevalence was observed in individuals aged 50–59 years (30–39 years in men, 50–59 years in women), and the number of diagnoses showed an increasing trend. Lung involvement was the most common (93.5%), followed by the skin, eyes, and extrathoracic lymph nodes. Among patients with lung involvement and a follow-up period of ≥ 3 months, 66.8%, 31.0%, and 2.2% showed improvement, stability, and progression, respectively. Eleven patients (2.9%) died, and the 5-year survival rate was 99%. The number of diagnosed cases showed an increasing trend, and the mean age at diagnosis was increased compared with that in previous reports. Organ involvement was similar to that of Westerners, although the prognosis appeared better.